Validity Testing of Developed General English Modul for University Students at Universitas PGRI Silampari - Yulfi Yulfi; Ayu Oktaviani; Rahmatika Sri Dewi Rizki (Linguistic, English Education and Art (LEEA) Journal, 2023)
This research aimed to find out the expert validity of developed modul â€œGeneral English Modulâ€ at PGRI Silampari University (UNPARI). The method used in this research was descriptive qualitative. There were three experts in validating the modul. They were expert of content, expert of instructional design and expert of media. The instrument used in collecting data was questionnaire. In analyzing data, the researchers read all comments given by experts for each espertise (data condensation). After that, the coment was interpreted by the researchers and rechecked to the experts (data display). Finally, the developed modul was revised based on the suggestion. For the results showed that for content validity, the expert coclude that the modul was in highly validity, but she suggested some revision. In validating instructional design, the expert also received the modul but with some revisions. And the last, there were some aspect of media such as the brightness of the cover, pictures and color must be revised. Finally, in conclusion, the modul of General English subject at UNPARI was accepted with some revision. Keywords: General English Modul, Validity